Taxonomic classification of the reef coral family Lobophylliidae (Cnidaria: Anthozoa: Scleractinia). (14th October 2016) - Huang, Danwei; Arrigoni, Roberto; Benzoni, Francesca; Fukami, Hironobu; Knowlton, Nancy; Smith, Nathan D.; Stolarski, Jarosław; Chou, Loke Ming; Budd, Ann F.
Abstract : Lobophylliidae is a family‐level clade of corals within the 'robust' lineage of Scleractinia. It comprises species traditionally classified as Indo‐Pacific 'mussids', 'faviids', and 'pectiniids'. Following detailed revisions of the closely related families Merulinidae, Mussidae, Montastraeidae, and Diploastraeidae, this monograph focuses on the taxonomy of Lobophylliidae. Specifically, we studied 44 of a total of 54 living lobophylliid species from all 11 genera based on an integrative analysis of colony, corallite, and subcorallite morphology with molecular sequence data. By examining coral skeletal features at three distinct levels – macromorphology, micromorphology, and microstructure – we built a morphological matrix comprising 46 characters. Data were analysed via maximum parsimony and transformed onto a robust molecular phylogeny inferred using two nuclear (histone H3 and internal transcribed spacers) and one mitochondrial (cytochrome c oxidase subunit I) DNA loci. The results suggest that micromorphological characters exhibit the lowest level of homoplasy within Lobophylliidae. Molecular and morphological trees show that Symphyllia, Parascolymia, and Australomussa should be considered junior synonyms of Lobophyllia, whereas Lobophyllia pachysepta needs to be transferred to Acanthastrea . Our analyses also lend strong support to recent revisions of Acanthastrea, which has been reorganized into five separate genera ( Lobophyllia, Acanthastrea, Homophyllia, Sclerophyllia, and Micromussa ), and to the establishment of Australophyllia . Cynarina and the monotypic Moseleya remain unchanged, and there are insufficient data to redefine Oxypora, Echinophyllia, and Echinomorpha . Finally, all lobophylliid genera are diagnosed under the phylogenetic classification system proposed here, which will facilitate the placement of extinct taxa on the scleractinian tree of life.